Percutaneous Kidney Biopsy Under Guidance of Ultrasound, A Point of Care Ultrasound Gift: A Review article: Real time US for kidney biopsy - Hassanzadeh Rad , Afagh; Badeli, Hamidreza (Journal of Pediatric Nephrology, 2020)
After the application of autopsy as the only method for assessing pathophysiology of renal disease, over 50 years ago, the kidney biopsy has become an essential tool for diagnosis and management of renal diseases. To perform an appropriate kidney biopsy, some steps should be considered. In this review, the authors aimed to mention thorough details regarding percutaneous kidney biopsy under the guidance of ultrasound.